2016
DOI: 10.1002/cncr.30181
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy is associated with improved survival in patients with stage II colon cancer

Abstract: Background The role of adjuvant chemotherapy in patients with stage II colon cancer remains to be elucidated and its use varies between patients and institutions. Currently, clinical guidelines suggest discussing adjuvant chemotherapy for patients with high-risk stage II disease in the absence of conclusive randomized controlled trial data. In order to further investigate this relationship, the study aimed to determine whether an association exists between overall survival (OS) and adjuvant chemotherapy in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 34 publications
(54 reference statements)
10
122
2
3
Order By: Relevance
“…26 Though limited by follow-up and sample size, in this cohort of patients with stage II colon cancer there was not a clear association of chemotherapy and survival, whereas in our analysis of over 150,000 patients in the National Cancer Database (NCDB), adjuvant chemotherapy was found to be associated with improved OS. 16 Reasons for this difference may include improved quality of surgery in the studied cohort and less stage migration, as evidence by only 17.2% of patients who had <12 nodes evaluated in the current study as compared to 45% in the study utilizing the National Cancer Database. 27, 28 In addition, despite propensity matching, unmeasured selection bias was acknowledged as a limitation of the NCDB study which may have affected the association of survival with chemotherapy use.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…26 Though limited by follow-up and sample size, in this cohort of patients with stage II colon cancer there was not a clear association of chemotherapy and survival, whereas in our analysis of over 150,000 patients in the National Cancer Database (NCDB), adjuvant chemotherapy was found to be associated with improved OS. 16 Reasons for this difference may include improved quality of surgery in the studied cohort and less stage migration, as evidence by only 17.2% of patients who had <12 nodes evaluated in the current study as compared to 45% in the study utilizing the National Cancer Database. 27, 28 In addition, despite propensity matching, unmeasured selection bias was acknowledged as a limitation of the NCDB study which may have affected the association of survival with chemotherapy use.…”
Section: Discussionmentioning
confidence: 66%
“…16 However, information on patient selection, specific chemotherapy agent, disease recurrence, and certain high-risk pathologic features was not available in this database. Therefore, we identified 7 participating large academic-affiliated and community-based institutions in the Advocate healthcare system, the largest fully integrated healthcare network in the state of Illinois that diagnoses and treats more cancer patients than any other system in Illinois, to address these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Due to harmful side-effects, low-risk patients who received adjuvant chemotherapy had worse survival. In Japan, adjuvant chemotherapy led to no improvement in RFS in high-risk patients [6], but a US registry study with over 153,000 stage II colon cancer patients having surgery in 1998-2011 showed that both low-and high-risk patients benefitted from adjuvant chemotherapy [20]. In this US study, choice of recipients of adjuvant chemotherapy was largely dependent on socioeconomic status and health care insurance, both introducing major bias.…”
Section: Most Stage II Patients Should Not Be Offered Adjuvant Chemotmentioning
confidence: 85%
“…In this US study, choice of recipients of adjuvant chemotherapy was largely dependent on socioeconomic status and health care insurance, both introducing major bias. It is noteworthy that 5-year overall survival (OS) for all stage II patients was 81%, low-risk stage II patients without adjuvant chemotherapy had a 5-year OS of only 68%, whereas for those receiving it, OS was 86% [20]. One Italian study concentrating solely on pT3N0 reported that adjuvant-treated (AC) patients did much better than did those without it, with no major differences between low-and high-risk (RFS for AC low-risk 87% and high-risk 83%, versus no AC low-risk 75%, high-risk 71%) [21].…”
Section: Most Stage II Patients Should Not Be Offered Adjuvant Chemotmentioning
confidence: 99%
“…Esto ha servido, también, para elegir los tratamientos adyuvantes en el control de la enfermedad 75 . Sin embargo, en los últimos años, herramientas moleculares como el estado MSI: inestabilidad de microsatélites; CIMP: fenotipo de metilación de islas de CpG del gen KRAS tumoral, han permitido predecir e identificar pacientes que se van a beneficiar de la utilización del tratamiento biológico 76,77 .…”
Section: Gen Kras Y Clasificación Tnmunclassified